Monetary and fiscal policy dynamics in an asymmetric monetary union - Volker Clausen; Hans-Werner Wohltmann (Universität-Gesamthochschule Essen, Fachbereich Wirtschaftswissenschaften, 2002)
This paper investigates the dynamic effects of monetary and fiscal policy in a monetary union, which is characterized by asymmetric interest rate transmission. This asymmetry gives rise to intertemporal reversals in the relative effectiveness of policy on member country outputs. The direction and the number of these reversals depend on whether policies are unanticipated or anticipated. We also study the coordination between monetary and fiscal policy in a monetary union. Monetary policy may completely stabilize European output after unanticipated fiscal policy shocks. With anticipated fiscal policy shocks, complete stabilization throughout the overall adjustment process requires monetary policy to be time-inconsistent.
Keywords: E58; 330; European Monetary Union; fiscal policy; monetary policy; policy coordination; spillover effects; time inconsistency; Geldpolitik; Finanzpolitik; Währungsunion; Zwei-Länder-Modell; Konjunkturzusammenhang; Zeitkonsistenz; Internationale wirtschaftspolitische Koordination; Europäische Wirtschafts- und Währungsunion; Theorie